1999
DOI: 10.1007/s000400050128
|View full text |Cite
|
Sign up to set email alerts
|

Intraspecific colony recognition in the termites Macrotermes subhyalinus and Macrotermes bellicosus (Isoptera, Termitidae)

Abstract: Intraspecific colony recognition in the termites Macrotermes subhyalinus and M. bellicosus was investigated over two field seasons in Comoë-Nationalpark (Ivory Coast). Behavioural tests with major workers and minor soldiers, respectively, were performed using neutral arenas of covered plastic dishes. For each species, termites were sampled by baiting from 10 field colonies randomly chosen at four different sites. Major workers and minor soldiers of both species were capable of differentially discriminating bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
24
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 33 publications
4
24
0
Order By: Relevance
“…Therefore, alarm and overt aggression were investigated between major workers in an arena experiment. Jmhasly & Leuthold (1999b) showed that the results of such arena experiments are correlated between castes and that the results of the experiments correspond to the field situation. In consequence, the conclusions from the experiments presented here should not depend on the chosen caste and should not be an artefact of the experimental situation.…”
Section: Behavioural Testsmentioning
confidence: 87%
See 4 more Smart Citations
“…Therefore, alarm and overt aggression were investigated between major workers in an arena experiment. Jmhasly & Leuthold (1999b) showed that the results of such arena experiments are correlated between castes and that the results of the experiments correspond to the field situation. In consequence, the conclusions from the experiments presented here should not depend on the chosen caste and should not be an artefact of the experimental situation.…”
Section: Behavioural Testsmentioning
confidence: 87%
“…subhyalinus, Jmhasly et al, 1998;Jmhasly & Leuthold, 1999b). In M. subhyalinus, the level of aggression between colonies varies considerably (Jmhasly & Leuthold, 1999b). This cannot be explained by the age of colonies or geographical distance.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations